Preparation and properties of anti-static coating on the 3Y-TZP ceramics. Issue 14 (1st October 2018) - Yang, Xianfeng; Ni, Zhentao; Yang, Xiaole; He, Qinglong; Xie, Hehan; Xu, Xiewen; Xie, Zhipeng
Abstract: Anti-static coating on the 3Y-TZP ceramics was prepared through adding ZnO and SnO2 to the glaze. Wettability and surface resistivity of the coating was studied. Dissolving, crystallization and distribution of ZnO and SnO2 in the coating were analyzed. Static dissipative mechanism of the coating was explored. The results showed that the interface bonding and wetting between the coating and 3Y-TZP were perfect. The surface resistivity of the coating could be reduced to 10 7 Ω/□. ZnO was helpful to improve the wettability of the coating and inhibit the crystallization of the SiO2 . ZnO and SnO2 dissolved in the glaze and the semi-conductive composition rich melt layer around SnO2 was formed. The melt layer contacted each other and the static dissipative network was established, which attributed to the anti-static properties of the coating.